Assessment of retired elderly's people autonomy and its affecting factors in Rasht - Nasrin Masoumi; Shirin Jafroudi; Atefeh Ghanbari Khanghah; Ehsan Kazemnejad Leili (Guilan University of Medical Sciences, 2011)
Introduction: In elderly, autonomy is threatened due to physical and mental disability. This ‎disability in activity of daily living is a chronic condition that causes cost disbursement in ‎society and reduce older people s quality of life. ‎ Objective: The aim of this study is to determine and compare retired elderly s ability in ‎activity of daily living based on demographic characteristics in Rasht.‎ Methods: This study is a cross- sectional descriptive study that includes ‎‏194‏‎ retired elders in ‎governmental organizations. Data collection is done by Katz questionnaire and for assessment ‎of activity of daily‏ ‏living (ADL) ability and instrumental activity of daily living (IADL) ‎Lawton questionnaire was used. Collected data were analyzed using SPSS version ‎‏16‏‎.‎ Results:‎‏ ‏Study results showed that although elderly needed help in activity of daily living ‎such as bathing, walking and appearance conditions but‏ ‏none were in completely dependent ‎group after scoring. In independency domain in instrumental ADL, ‎‏86‏‎.‎‏6‏‎% of them were ‎independent, ‎‏10‏‎.‎‏3‏‎% of them needed help and ‎‏3‏‎.‎‏1‏‎% of them were completely dependent. In ‎demographic characteristics, autonomy in activity of daily living correlates with age, marital ‎status, education and illness.‎ Conclusion: Because of significant correlation between disability in activity of daily living by ‎increasing age, female gender and morbidity, planning for education classes, providing posters ‎and pamphlet based on life style correction and prevention of musculoskeletal diseases is an ‎important step in getting elders to effective and healthy life.‎